Solidarity Through the Visual: Healing Images in the Brussels Terrorism Attacks. Issue 6 (2nd November 2017) - Berkowitz, Dan
Abstract : This study applies a semiotic lens to argue that news media are not only conveyors of images of terrorism but, through a combination of photographs, editorial cartoons, and anchoring texts, have the potential to serve as facilitators of healing and solidarity in both the local and the global media arena. This anchoring function is essential for audience decoding—especially in the global—because many photographs and cartoons are culturally bound and therefore not readily accessible to the broader audience. Through the information they provide, written texts help to anchor meanings of the visual texts, conveying a sense of solidarity against terrorism.